2022
DOI: 10.3389/fphar.2022.952337
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of menthol against sepsis-induced hepatic injury: Role of mediators of hepatic inflammation, apoptosis, and regeneration

Abstract: Liver dysfunction in sepsis is a major complication that amplifies multiple organ failure and increases the risk of death. Inflammation and oxidative stress are the main mediators in the pathophysiology of sepsis. Therefore, we investigated the role of menthol, a natural antioxidant, against sepsis-induced liver injury in female Wistar rats. Sepsis was induced by cecal ligation and puncture (CLP). Menthol (100 mg/kg) was given intragastric 2 h after CLP. Blood samples and liver tissues were collected 24 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Previous studies have demonstrated that hepatocyte death by apoptosis mechanism serves a crucial role in septic liver injury. 30,31 Conversely, inhibiting liver apoptosis can relieve septic liver injury. 32 Cleaved caspase-3 is a hallmark of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hepatocyte death by apoptosis mechanism serves a crucial role in septic liver injury. 30,31 Conversely, inhibiting liver apoptosis can relieve septic liver injury. 32 Cleaved caspase-3 is a hallmark of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis, characterized by an overwhelming host response to infection, significantly impacts multiple organs, including the liver, kidneys, and heart. Liver damage in sepsis is a key factor in patient mortality, necessitating prompt and effective treatment strategies [ 12 , 13 ]. Excessive inflammatory response and oxidative stress play pivotal roles in the pathogenesis of liver injury, making them key targets for therapeutic intervention [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a lipid peroxidation marker, MDA reacts with thiobarbituric acid in an acidic medium to form a colored adduct with maximal absorbance at 534 nm; the measured values were proportional to the amount of lipid peroxides [ 66 ]. Cardiac GSH was determined based on its ability to react with 5,5′-dithio-bis-2-nitrobenzoic acid (Ellman’s reagent) and form a yellow product [ 65 , 67 ]. Tissue NOx was determined as an indicator of cardiac • NO content.…”
Section: Methodsmentioning
confidence: 99%